Lima city and its transit towards the abyss in the movie Videophilia (and other viral syndromes) - Cabrejo, José Carlos (E|C, 2021)
The movie Videophilia (and Other Viral Syndromes) (2015) showcases shots of the city of Lima, overlapped by Internet images: gif files, YouTube videos, porn sites, videogames, etc. The feature film by Juan Daniel Molero states that the Peruvian capital city does not assimilate the Internet, and that it actually happens the other way around, with the Net absorbing the city, as a space that disappears within a black hole. Thus, it is important to interpret this vision of Lima through the space regimes proposed by Eric Landowski: the abyss, in regards to the online world in which the city loses itself; the volute, a domain centered around the contact between bodies that are bound to be represented on a video world; the fabric, a zone in which the young characters mediate their relationship with the city through television and cell phone screens, and the net, present across the technological and erotic manipulations that take place between the characters.